Perspectives from remote sensing to investigate the COVID-19 pandemic: A future-oriented approach - Mehmood, Khalid; Bao, Yansong; Mushtaq, Sana; Saifullah,; Khan, Muhammad Ajmal; Siddique, Nadeem; Bilal, Muhammad; Heng, Zhang; Huan, Li; Tariq, Muhammad; Ahmad, Sibtain (Frontiers in Public Health, 2022)
With progress in space science and scientific technology, remote sensing has surfaced as an innovative solution to alleviate the challenges of the COVID-19 pandemic. To unfold the research features and growth trends in employing remote sensing for monitoring and managing the COVID-19 research, a bibliometric analysis was conducted on the scientific documents appearing in the Scopus database. A total of 1509 documents on this topic were indexed between 2020 and 2022, covering 165 countries, 577 journals, 5239 institutions, and 8616 authors. The studies related to remote sensing and COVID-19 have a significant increase of 30% with 464 articles. Statistical analysis of total publication (TP) and total citation (TC) revealed a significant correlation. The United States (429 articles, 28.42% of the global output), China (295 articles, 19.54% of the global output), and the United Kingdom (174 articles, 11.53%) appeared as the top three most contributions to the literature related with remote sensing and COVID-19 research. Sustainability, Science of the Total Environment, International Journal of Environmental Research and Public Health, were the three most productive journals in this research field. The utmost predominant themes are COVID-19, remote sensing, spatial analysis, coronavirus, lockdown, and air pollution. The expansion of these topics appears to be associated with cross-sectional research on remote sensing, evidence-based tools, satellite mapping, and geographic information systems. The recent developments in the use of remote sensing technology in managing COVID-19 will help monitor and manage similar global pandemic risks in the coming years.